Experimental characterization of the use of the wave energy convertor DIKWE as a breakwater reinforcement on the existing structure performances (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Climate change is forcing ports transformation. First, they must tackle carbon emissions and engage in their own energy transition. As big energy and fossil fuels consumers, ports can test and demonstrate the viability of low-carbon energy solutions. Second, the effects of climate change on weather conditions must be anticipated and addressed. Sea level rise, higher waves and stronger winds will increase the loads on ports infrastructures. Therefore, new protections might be required, and existing structures need to be reinforced.Based on these needs, WaveOp* has developed since 2019 the technology DIKWE: a breakwater structure integrating a wave energy convertor. The system is split into modules, each one being equipped with a flap whose axis is on top and oscillating under the action of waves. The movement of the flap is converted into hydraulic pressure, and then into electricity. The technological development of the solution was carried out together with the French scientific institute IFREMER. This scientific collaboration demonstrated the high energy conversion performances of the technology through the installation and study of a prototype in Saint-Anne-du-Portzic (Brittany, France) between May 2022 and May 2023 [Le Boulluec et al, 2024].The technology has been developed to address the different configurations faced by ports: it can either be designed as a new independent structure offering an additional protection to the harbour or designed as a reinforcement of an existing breakwater. A DIKWE device installed in front of or integrated into an existing breakwater acts as a buffer to wave loads.Flume tests were carried out in June 2024 in the Laboratoire Ondes et Milieux Complexes in Le Havre, France (LOMC) to characterize the impact of DIKWE devices on the protective functions of an existing breakwater. Different integration solutions are modelled at a 1:35 scale and tested under extreme sea states for varying water depths and hydrodynamic forcings. In total XXX tests are performed. They are compared to the reference situation of the bare breakwater. Damage is calculated to measure the impact of the device on the structural behaviour of the existing breakwater. Overtopping is measured to estimate the benefit brought by the device on its hydraulic performance. In addition, fluid dynamics inside one of the module and the flap’s motion are recorded.The aim of this paper is to expose the methodology and the results of the tests. Significant reductions in damage and overtopping are shown for the three integration solutions tested. The energy efficiency of the technology was already established in 2022 [Le Boulluec et al, 2024], this present set of tests demonstrates the reinforcement capacity of the system on an existing structure. The installation of a scale 1:1 demonstrator composed of 3 modules and used as a reinforcement solution is planned for summer 2025 on the French coastline.* WaveOp is a joint venture company cocreated by the Groupe Legendre and Geps Techno